GAMES THAT TEACH : EXPERIMENTAL ACTIVITIES FOR REINFORCING TRAINING - SUGAR, Steve (Jossey-Bass Pfeiffer San FranciscoUS, 1998)
Offers 26 interactive games and exercises for reviewing anf reinforcing training content, and a seven-step game implementation model. Presents each game in a structured format with the following elements: purpose, supplies, steps, customising and scoring instructions. Includes player instruction sheets and sample game sheets. Games cater for : teams of various sizes; practising negotiatioon; using strategic thinking; and, practising teamwork etc.